Insurance Sector & Consumer Protection: The Nationalization of the Insurance Sector in India: Implications for Consumer Protection and Industrial Development (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The  Governmentof  India in  1956,  brought together  over  240 private  life insurers and  provident societies  under  one nationalized  monopoly corporation  and Life  Insurance Corporation (LIC)was born. Nationalization was justified on the grounds that it would createmuch-needed funds for rapid industrialization. This was in conformity with theGovernment's chosen path of State lead planning and development.